2017
DOI: 10.1159/000477675
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hyponatremia and Its Associated Morbimortality in Hospitalized Patients Receiving Parenteral Nutrition

Abstract: Background: The objective of the study was to determine the prevalence of hyponatremia (HN) and its associated morbimortality in hospitalized patients receiving parenteral nutrition (PN). Methods: A retrospective study including 222 patients receiving total PN (parenteral nutrition group [PNG]) over a 7-month period in a tertiary hospital and 176 matched to 179 control subjects without PN (control subjects group [CSG]). Demographicdata, Charlson Comorbidity Index (CCI), date of HN detection-(serum sodium or SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…Early studies confirmed that hyponatremia is the most likely cause of deterioration and increased mortality associated with various internal environmental disorders [ 12 , 13 , 35 , 36 ]. In a study of 53,236 hospitalized patients, Wald et al noted reduced survival rates and prolonged hospitalization times among patients with CAH and HAH [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies confirmed that hyponatremia is the most likely cause of deterioration and increased mortality associated with various internal environmental disorders [ 12 , 13 , 35 , 36 ]. In a study of 53,236 hospitalized patients, Wald et al noted reduced survival rates and prolonged hospitalization times among patients with CAH and HAH [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Winzeler et al found that serum sodium was positively correlated with mortality, and serum sodium < 125 mmol/L was significantly correlated with 1-year mortality, recurrence rate of hyponatremia, and readmission rate [ 12 ]. Gomez-Hoyos et al found that hyponatremia is associated with increased mortality and morbidity [ 13 ]. However, there is still some debate over how much of the increased risk of death is directly attributable to hyponatraemia, and how much is due to under-lying disease.…”
Section: Introductionmentioning
confidence: 99%
“…[1] P-Na is also associated with increased mortality and morbidity. [2] It is uncertain however as to whether patients with P-Na tend to be elderly and whether the mortality risk is related to the degree of P-Na. [3,4]…”
Section: Introductionmentioning
confidence: 99%
“…Sailer and colleagues mentioned malnutrition as a known risk factor for hyponatraemia. Generally speaking, hyponatraemia is often found in conditions associated with lower food intake (e.g., in patients with tumours, alcoholism, anorexia nervosa, very advanced age, or in intensive care units) [4], and is more prevalent in patients on parenteral nutrition [5]. It should thus not be surprising that patients with hyponatraemia often exhibit additional electrolyte abnormalities unrelated to the arginine vasopressin secretion (e.g., hypophosphataemia, hypokalaemia, or hypomagnesaemia) [6].…”
mentioning
confidence: 99%